Effect of frothers on removal of unburned carbon from coal-fired power plant fly ash by froth flotation. Issue 3 (11th February 2018) - An, Maoyan; Liao, Yinfei; Zhao, Yifan; Li, Xiaoheng; Lai, Qingteng; Liu, Zechen; He, Yucheng
ABSTRACT: The effect of single frothers and their blends on bubble size, froth stability, and unburned carbon (UC) flotation performance was studied. Methyl isobutyl carbinol that produces smaller bubbles is efficient in floating ultrafine particles and producing concentrate. DF-250 that gives higher froth stability is effective for recovering coarse particles and improving recovery. The presence of DF-250 in the blend increases bubble size and significantly enhances froth stability, and hence the optimal flotation performance is achieved with 75% DF-250. It indicates that the frother giving high froth stability is better in UC flotation due to the little effect of UC on froth stability.